Role of the impurities in 2D spin crossover nanoparticle: Monte Carlo study - Ivashko, V.; Krulikovskyi, O.; Samila, A. (Physics and Chemistry of Solid State, 2023)
This work is devoted to the study of the impurities effect in 2D spin crossover nanosystem in frame work of an Ising-like model. Results were obtained by means of Monte Carlo modeling technique, based on the heat bath algorithm. It is shown, that the impurities change the system’s thermal hysteresis width and shift the spin transition curves (HS → LS). In this manner, impurities can act as an additional influence parameter on the transition curves. The considered effect is not significant, but nevertheless should be taken into account in the developing process of nanoscale devices based on spin crossover compounds.